Is it possible that our generation will deal a new pandemic caused by another Coronavirus? - Miller, Michael Edward (2022)
The current COVID-19 pandemic was induced by the emergence of a coronavirus from an animal as a reservoir. Thus, it is of great importance to know how the evolution of these viral agents occurs in the nature. In this article, the main mechanisms associated with the evolution of coronaviruses were presented, indicating the animal species that act as reservoirs or evolutionary hosts, the viral genetic mechanisms involved in the generation of viral variants, the contribution of human actions to generate recombinant coronaviruses with pandemic potential. From the points discussed in the article, we conclude that the generation of new coronaviruses can be avoided with the implementation of public policies that propose health actions and thus there will only be human health if there is environmental health and animal health.